Analisis bibliometrik dari penelitian desain didaktis di sekolah dasar - Sari, Indah Puspita; Supriyadi, Edi; Suryadi, Didi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
By using bibliometric analysis with Biblioshiny and computational mapping with VOSviewer, the purpose of this investigation is to investigate the evolution of research on didactic design in primary schools. In order to obtain data from the Dimension software, which served as a reference manager, we searched the titles and abstracts of papers for the terms "didactical design" and "primary school." The search was conducted on March 3, and it turned up 110 documents that matched the criteria and had a publishing range of 2016 to 2023. Articles and proceedings were found to be the sources that were referred to the most frequently, with a total of 18,094 citations and an average of 18.11 citations per article. The average h-index and g-index for all articles were 61 and 109, respectively. Additionally, the data from the findings show that research on didactic design in elementary schools has been widely conducted and is continuing to increase, indicating that it has a good chance of being associated with other significant terms in the years to come, both in the current year and in the future.